2016
DOI: 10.1111/epi.13424
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the epilepsy nurse: Results of a randomized controlled study

Abstract: SUMMARYObjective: We investigated the efficacy of epilepsy nurses on satisfaction with counseling about epilepsy in a randomized, controlled, prospective trial. Methods: Patients with epilepsy treated by neurologists in outpatient clinics were consecutively enrolled and randomly allocated to either the epilepsy nurse (EN) group (n = 92) or the control group (n = 95). Patients in the EN group were advised according to their needs by epilepsy nurses. The control group received routine care without additional cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 35 publications
3
51
0
8
Order By: Relevance
“…3,5,7 The challenge ahead of us is to integrate these different therapies in busy clinical practice. 12,13 Different models of practice can be trialed and adopted for the efficient management of the neuromodulation clinic. Having a specialized neuromodulation clinic allows efficient management of resources like scheduling field engineers to attend the clinic and to avoid multiple visits within a week.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,7 The challenge ahead of us is to integrate these different therapies in busy clinical practice. 12,13 Different models of practice can be trialed and adopted for the efficient management of the neuromodulation clinic. Having a specialized neuromodulation clinic allows efficient management of resources like scheduling field engineers to attend the clinic and to avoid multiple visits within a week.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis was that other measures, such as self-mastery, medication adherence and seizure frequency, could improve with increased knowledge. In the UK and other European countries, epilepsy nurses are taking an increasing role reinforcing advice about self-management [4345] which could reduce the impact of memory issues. Self-management education, which is reinforced over time by a co-intervention of advice from a nurse or other professional, seems more likely to promote QoL [16, 43, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 15 RCTs investigating educational interventions, 4 studies were LOE II, 4 studies were LOE III, and 7 studies were LOE IV. All 4 LOE II studies reported improvements in their various primary outcomes: medication adherence, epilepsy knowledge and satisfaction with information and support, medication‐related problems, and HRQOL .…”
Section: Available Evidence For Psychological Treatment Across the Epmentioning
confidence: 99%
“…Only 1 RCT investigated a psychological intervention specifically aiming to decrease anxiety symptoms . Four studies investigating psychological interventions, 1 study investigating a self‐management program, and 1 study investigating an educational program measured anxiety symptoms as a secondary outcome. Three studies were LOE II, and 1 study was LOE III, whereas the remaining 3 studies were LOE IV .…”
Section: Available Evidence For Psychological Treatment Across the Epmentioning
confidence: 99%
See 1 more Smart Citation